Pengaruh Penggunaan Sosial Media Instagram Dimasyarakat Kampung Kandaga - Sandi Gustiandi; Tedi Kurniadi; Ahmad Rianda Lubis; Neng Aas Fauziah Rohmah (Kampret Journal, 2022)
Path occupies the fourth position with the dominance of users ranging in age from 20 to 25 years. We will conduct research in the form of a survey. The survey is a quantitative basic form". The object of this research is "The Influence of Instagram Social Media Use in the Kandaga Village community". Researchers conducted a survey on the influence of Instagram social media use in the Kandaga village community. Our group used a survey with questionnaire research which was used to collect research data containing questions and statements answered by respondents. In addition, other words of influence are a state of reciprocity, or a causal relationship between what affects and what is influenced. The Internet significantly influences the way people live by changing because of its technology. We get There are 12 informants who use Instagram among teenagers and we asked some questions regarding the influence of Instagram media.There are 80% of them prefer to interact with friends face to face or directly and 70% of them get information and insight from them. he's the instagram.